Think-Pair-Share (TPS) Type Cooperative Learning Can Increase Learning Outcomes on Healthy Living Culture Materials - Ketut Kartika, Gusti (International Journal of Management and Education in Human Development, 2021)
Student learning outcomes in science subjects, especially in the material for healthy living culture, the results are still low. This is because the teacher has not implemented a learning model that stimulates student interest in learning. Various efforts have been made by the teacher but have not been able to show optimal results. Through this research, the Think-Pair-Share (TPS) type of cooperative learning model is applied in the hope of increasing student activity which in turn can also improve their learning outcomes. The formulation of the problem in this study is: "Can the learning outcomes of eighth grade students of SMPN 22 South Konawein the material of Healthy living culture be improved through the application of Think-Pair-Share (TPS) type cooperative learning model. The purpose of this study was to improve the science learning outcomes of eighth grade students of SMPN 22 South Konaweon the material of healthy living culture through the application of the Think-Pair-Share (TPS) type of cooperative learning model . The benefits of this research for students, researchers and other teachers. This type of research is classroom action research. The implementation of this classroom action research consists of 2 cycles. Each cycle is carried out according to the changes to be achieved such as what has been designed in the investigated factors. The procedures for this classroom action research are: 1) planning, 2) implementing actions, 3) observing and evaluating, 4) reflection. The data sources of this research are students and teachers. The types of data obtained are quantitative and qualitative data, through observation sheets and learning outcomes tests. How to collect data about the conditions of implementation of the TPS type cooperative learning model was taken using teacher and student observation sheets, data about learning outcomes was taken using a learning outcome test evaluation tool. From the results of observations, evaluations and reflections in each cycle, it can be concluded that the learning outcomes of VIII grade students of SMPN 22 South Konaweon the material of Healthy Living Culture can be improved through the application of the Think-Pair-Share (TPS) cooperative learning model . In the implementation of the second cycle classically, 28 students (87.5%) scored 70 with an average score of 80.94. This has increased when compared to the classical first cycle of students who scored 70 as many as 14 people (43.75%) with an average score of 60.63.